Is the use of a powered dermatome an aerosol-generating procedure (AGP)? Implications for personal protection against COVID-19 virus - Kayvan Shokrollahi; Ioannis Kyriazidis; Shomari Zak-Williams; Claire Jones; Elisa Murgatroyd; Dilnath Gurusinghe (SAGE Publishing, 2020)
Introduction: Many healthcare workers have contracted SARS-CoV-2 during the pandemic, many cases of which have resulted in severe illness and death. No studies have assessed the potential for powered dermatomes to generate aerosol, an essential technique in burns and plastic surgery. The primary aim of the present study was to capture video footage to illustrate the potential for a powered dermatome to generate significant spray and hence aerosol. Methods: We utilised a simulated skin graft harvest experimental method. Fluorescein-stained saline was used with ultraviolet (UV) backlighting to demonstrate fluorescent spray from a popular brand of air-powered dermatome. Ultra-slow-motion (960 frames/s) video was used to demonstrate the oscillation of the dermatome blade and the origin within the machine of any spray generated, and the extent of spray generated. Results: The key finding from this study is the captured video footage linked with this paper. Droplets of various sizes are seen spraying out from the leading edge at the sides where the blade oscillates. UV backlighting provides a clear demonstration of the dermatome generating fine spray. Conclusion: Our study demonstrates that powered dermatome usage is likely to generate aerosol from blood or blood-contaminated fluid, but does not demonstrate or quantify to what extent this may be clinically relevant in terms of viral transmission potential. We suggest ways to reduce the risk of spray from dermatomes including limiting donor-site bleeding and avoiding a wet donor area. Lay Summary A dermatome is a device used by surgeons to harvest split skin grafts (SSGs). SSGs are an essential component of burns and reconstructive plastic surgery. Aerosol-generating procedures (AGPs) have implications for transmission of viruses including COVID-19. It has not previously been formally assessed whether use of a dermatome should be classified as an AGP. This study uses a fluorescent dye in the context of simulated surgery using a dermatome to see if any, and how much, fine spray is generated from the device and also utilises ultra-slow-motion videography to see how any spray may be generated. At the heart of this study is the included video footage that demonstrates considerable fine spray generation which suggests it is best to assume that dermatomes are likely to generate some degree of aerosol depending on the clinical scenario and how it is used. However, this information does not translate to providing any information about the risk of transmission of the virus from using a dermatome, especially in relation to COVID-19, and separate research would be required to answer this.